2007
DOI: 10.1179/174367607x156016
|View full text |Cite
|
Sign up to set email alerts
|

Electrical conductivity of TiO2within n–p transition Part II – Electrical conductivity components

Abstract: The present paper reports the electrical properties of undoped TiO 2 single crystal in terms of the conductivity components for electrons, holes and ions and the related transference numbers within the n-p transition regime. These data indicate that ionic conductivity in TiO 2 may assume a substantial value, which cannot be ignored. The minimum of the electrical conductivity at the n-p transition and its electronic component, were used for the determination of the band gap, which is 3 . 13 and 3 . 1 eV respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…in the form of a labelling threshold for contaminations of seed. 333 Indeed, this weakens the legal security in some countries since the leeway leads to contradictory decisions by the different authorities. Thus, over many years, a bitter discussion about introducing a threshold for GMOs in seed has been led most controversially.…”
Section: Threshold Valuesmentioning
confidence: 99%
See 1 more Smart Citation
“…in the form of a labelling threshold for contaminations of seed. 333 Indeed, this weakens the legal security in some countries since the leeway leads to contradictory decisions by the different authorities. Thus, over many years, a bitter discussion about introducing a threshold for GMOs in seed has been led most controversially.…”
Section: Threshold Valuesmentioning
confidence: 99%
“…423 In the Austrian Civil Code, 424 there is a provision similar to the one stipulated in the German Civil Code, whilst, however, in Austria there is -contrary to the legal situation in Germany -no adjudicated court ruling to date on whether incidents involving GMOs actually fall under the scope of this provision. 425 The liability rules stipulated by the Act on Genetic Engineering (Gentechnikgesetz, GTG) 426 are conceived as civil liability and encompass in its § 79 k a provision on the liability for the cultivation of GMOs that has been drafted particularly with a view to the agricultural use. 427 According to this provision, the owner or the authorised user of agricultural farming land may prohibit any emission of a farmer cultivating GMOs on the adjacent land insofar as these emissions exceed normal local levels and signifi cantly interfere with the usual use of the land.…”
Section: Civilmentioning
confidence: 99%
“…Laser beam can focus onto metallic surface to perform a broad range of treatments such as remelting, alloying and cladding, which are used to improve the wear and corrosion resistance of titanium alloys.Nowotny et al [4] and Galvan et al [5] reported that laser cladding is an economical and highly flexible repair technique which is already applied in the aero engine industry, e.g. to build-up worn tips of blades and labyrinth seals.…”
Section: Introductionmentioning
confidence: 99%